Metal-free oxidative cascade cyclization of isocyanides with thiols: a new pathway for constructing 6-aryl(alkyl)thiophenanthridines. Issue 22 (1st June 2016) - Yang, Ziqi; Song, Xiangyang; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Duan, Haifeng; Lin, Yingjie
Graphical abstract: Highlights: A metal-free pathway for forming 6-aryl(alkyl)thiophenanthridines is developed. This pathway is characterized by SH bond cleavage, then CS/CC bond formation. This reaction is suitable for a wide scope of substrates. Abstract: A metal-free pathway for constructing 6-aryl(alkyl)thiophenanthridines through oxidative cascade cyclization of isocyanides with thiols is developed. This pathway is characterized by SH bond cleavage of commercially available thiols, and subsequent CS/CC bond formation, which is suitable for a wide scope of substrates and by which a variety of 6-aryl(alkyl)thiophenanthridines could be synthesized in good to excellent yields.